Dental Implant Supported Restorations Improve Quality of Life in Osteoporotic Women - Christine DeBaz; Jenna Hahn; Lisa Lang; Leena Palomo (Hindawi Limited, 2015)
Introduction. The aim of this study is to compare the quality of life (QoL) in partially edentulous osteoporotic women who have missing teeth restored with dental implant retained restorations with those who do not and, secondarily, to report the rate of osteonecrosis in this sample. Methods. 237 participants completed the Utian QoL survey, a 23-question document measuring across psychosocial domains of well-being including occupational, health, emotional, and sexual domains which together contribute to an overall score. The subset of participants having dental implant supported prosthesis (64) was compared to the subset having nonimplant supported fixed restorations (47), the subset having nonimplant supported removable restorations (60), and the subset having no restoration of missing teeth (66). Results. ANOVA showed significant difference in all QoL domains between the four subsets (p<0.05). Although 134 reported oral bisphosphonate and 51 reported IV bisphosphonate use, no signs of ONJ were identified in any participants. Conclusion. These findings show implant retained oral rehabilitation has a statistically significant impact over nonimplant and traditional fixed restorations, removable restorations, and no restoration of missing teeth in far reaching areas including occupational, health, emotional, sexual, and overall QoL. These findings also support future examination of psychosocial outcomes associated with oral rehabilitation and the incorporation of oral health into women's health promotion.